Development Of Maharah Qira'ah Evaluation Tool Using Moodle For Eighth Graders at MTs - Khairani Fadhilah; Rahmawati Rahmawati (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
Evaluation is the main component in the teaching and learning process, these components ‎are objectives, materials, methods, evaluation. The good evaluation standards are; inclusivity of evaluation; continuity of evaluation;  objectivity; differentiation, and variety. Evaluation in the teaching and learning process is very ‎important because it uses various and different tools in evaluating reading skills learning to ‎find out how far their progress in learning to read. Evaluation as a data collection tool has ‎many tools, and these tools are tests and non-tests. The test as an assessment tool has ‎various types. One type is a written test and one of the tools in Moodle. the problem statement is ‎evaluation of reading skills in MTs has not used an evaluation tool with Moodle, students ‎are less enthusiastic in evaluating reading skills, and teacher lacks mastery technology. The ‎problem statement in this study is how to develop a reading skill evaluation tool using ‎Moodle for eighth grade in MTs?. The research method used is research and development ‎with 4D models (define, design, develop, disseminate) but the author limits it to the third ‎stage that is development. The results of this study are: (1) needs analysis includes analysis of the ‎‎2013 education curriculum, student books and the forms of tests used, analysis of the needs ‎of Arabic teachers and students (they really need the development of this tool) (2) Designing ‎a reading skill evaluation tool using Moodle includes writing a grid of questions, writing test ‎questions, and making evaluation tools in Moodle (3) The results of developing a reading ‎skill evaluation tool using moodle for eighth grade in MTs include the validity of linguists ‎and evaluations and media, and the results of all of them show very good ratings and this ‎means it is possible to use Moodle in the evaluation without correction